2023
DOI: 10.1210/clinem/dgad456
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Polygenic Scores for Differentiating Diabetes Diagnosis Among Patients With Atypical Phenotypes of Diabetes

Abstract: Aims To assess the clinical utility of two polygenic scores (PGSs) in differentiating between type 1/type 2 diabetes. Methods Patients diagnosed with diabetes in the UK Biobank were studied (N = 41,787), including 464 (1%) and 15,923 (38%) who met the criteria for classic type 1 and type 2 diabetes, respectively, and 25,400 (61%) atypical diabetes. The validity of two published PGSs for type 1 (PGST1D) and type 2 diabetes (PG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Second, the potential for clinical utility of polygenic prediction (and thereby the BPC approach) strongly depends on the magnitude of the PGS's R 2 liability , which is currently prohibitively small for most traits. However, there are some traits, such as cardiovascular disease and type 2 diabetes, for which current PGSs may already be sufficiently powered to find clinical application [41][42][43] and be economically effective [44][45][46][47][48][49] . Moreover, as GWAS sample sizes grow, the PGS's R 2 liability is expected to approach the disorder's h 2 SNP , and therefore their clinical applicability will become more likely.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the potential for clinical utility of polygenic prediction (and thereby the BPC approach) strongly depends on the magnitude of the PGS's R 2 liability , which is currently prohibitively small for most traits. However, there are some traits, such as cardiovascular disease and type 2 diabetes, for which current PGSs may already be sufficiently powered to find clinical application [41][42][43] and be economically effective [44][45][46][47][48][49] . Moreover, as GWAS sample sizes grow, the PGS's R 2 liability is expected to approach the disorder's h 2 SNP , and therefore their clinical applicability will become more likely.…”
Section: Discussionmentioning
confidence: 99%
“…The development and clinical implementation of polygenic risk score (PRS) is a core translational research focus of PMED. Initial efforts focused on prostate cancer PRS and its clinical validity in multiple ancestral populations ( Shi et al, 2021 ; Shi et al, 2022 ) and then expanded to additional conditions ( Ahmed et al, 2022 ; Wei et al, 2022a ; Glaser et al, 2022 ; Billings et al, 2023 ; Patel et al, 2023 ; Shi et al, 2023 ), including other cancer types ( Shi et al, 2019 ; Northcutt et al, 2021 ; Wei et al, 2022b ). Recently, our efforts have centered on the clinical implementation of PRS.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the well-documented large-effect HLA contribution, non-HLA susceptibility also plays a role 2 . Large-scale genome-wide association studies (GWAS) have identified dozens of independent non-HLA signals across the genome 1518 , that together with HLA polymorphisms can be used to construct polygenic scores (PGS) to evaluate genetic predisposition of T1D prior to the disease onset 1921 as well as better differentiate T1D from other types of diabetes 2224 .…”
mentioning
confidence: 99%